Function mechanism of turbulent eddy and process intensification of particle-bubble collision in fine mineral flotation - Xiaoheng LI; Hainan WANG; Kaixin ZHENG; Lijun WANG; Xiaokang YAN; Haijun ZHANG; Jiongtian LIU (Meitan xuebao)
The separation of fine minerals has always been a difficult problem in the mineral industry, and flotation is the main method for separating fine-grained minerals. Fine minerals have small mass, low inertia, and low kinetic energy. When encountering bubbles, fine particles are prone to flow around the streamline and are difficult to detach from the streamline and contact with bubbles. The low probability of collision with bubbles is one of the challenges in the flotation of fine particles. Strong turbulent flow can increase the kinetic energy of particles and the frequency of particle-bubble collision, which is a necessary condition for fine particle flotation. However, due to the high-frequency fluctuations and multi-scale eddy characteristics of turbulence, the movement and mineralization processes of particles and bubbles in the turbulent environment differ greatly from laminar flow, and the collision mechanism is not clear. In this study, the microscale dynamic behavior of fluids, particles, and bubbles in an isotropic turbulent field was measured using high-frequency particle image velocimetry and high-speed microscopic camera technology. With the help of mathematical methods such as wavelet transform, the multi-scale eddy characteristics of the turbulent flow field were mathematically decomposed, and the influence of small-scale eddy motion on the particle and bubble motion and collision processes was analyzed at the micro turbulence level. The study found that the motion of fine particles in the turbulent flow fields is constrained by the motion of small-scale turbulent eddies, and the scales of the two are correlated. In the scale scope of the study, the closer the Kolmogorov eddy scale generated by the flow field is to the particle size, the greater the particle slip velocity, and the greater the possibility of particle detachment from the streamline and collision with bubbles. Turbulent eddies briefly “capture” bubbles and affect their velocity and trajectory. Unlike conventional collision mineralization, particles locally follow micro-scale eddies during macroscopic motion with the mainstream flow field, while bubbles rotate with the eddy body in the high vorticity region and carry particles during their rotation. Bubbles and particles achieve mineralization through shear collision. Based on this, the vortex construction methods for the high vorticity small-scale eddy fields such as shock flow and vortex generators have been proposed, which enable the turbulent eddy motion of flow field in flotation to effectively act on fine particles, improve the probability of collision between fine particles and bubbles, and reduce the lower limit of effective recovery particle size in flotation. The flotation experiments of different types of pure minerals and actual minerals show that the flotation performance of fine mineral particles is effectively improved by regulating the turbulent eddies in the flow field. The study extends the fine mineral flotation process intensification from “particle adjustment”, “bubble adjustment”, and “reagent adjustment” to “eddy adjustment”, providing a new thought and method for the enhanced recovery of poor, miscellaneous and difficult-to-select mineral resources.